2021
DOI: 10.1186/s40035-021-00248-z
|View full text |Cite
|
Sign up to set email alerts
|

Language training for oral and written naming impairment in primary progressive aphasia: a review

Abstract: Background Primary progressive aphasia (PPA) is a neurodegenerative disorder characterized by a gradual, insidious and progressive loss of language abilities, with naming difficulties being an early and persistent impairment common to all three variants. In the absence of effective pharmacological treatments and given the progressive nature of the disorder, in the past few decades, many studies have investigated the effectiveness of language training to minimize the functional impact of word-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 128 publications
(437 reference statements)
1
24
0
Order By: Relevance
“…The decline in the language is expected in all three variants, and therefore, referral to a speech-language pathologist can be useful. Indeed, previous studies highlighted the efficacy of speech and language interventions for PPA patients, as well as maintenance of the gains after the treatment period [11,19,73,74]. Even teletherapy proved to be beneficial in mild-to-moderate cases, therefore opening the door to new possibilities and better access to therapy [75].…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the language is expected in all three variants, and therefore, referral to a speech-language pathologist can be useful. Indeed, previous studies highlighted the efficacy of speech and language interventions for PPA patients, as well as maintenance of the gains after the treatment period [11,19,73,74]. Even teletherapy proved to be beneficial in mild-to-moderate cases, therefore opening the door to new possibilities and better access to therapy [75].…”
Section: Discussionmentioning
confidence: 99%
“…It rather aims to offer a practical overview of commonly administered training strategies. See [ 66 ] for a review of methods used in svPPA studies up until 2014 and [ 23 ] for methods used in PPA studies in general.…”
Section: Figurementioning
confidence: 99%
“…The first rehabilitation reports emerged in the literature in the late 1990s, inspired by patients who spontaneously engaged in self-practice as an attempted remedy for their anomia [ 18 , 19 ]. The proliferation of single case studies and small group studies over the next decades have demonstrated that people with svPPA who receive naming therapy can improve their recall of object labels in the short term, that the gains might be retained over time and that at least partial restoration of semantic knowledge may be possible (see reviews by Carthery-Gouland et al [ 20 ], Jokel et al, [ 21 ], Cotelli et al, [ 22 ] and Pagnoni et al [ 23 ] for an overview). Furthermore, the breadth of research into non-pharmacological interventions has by no means remained restricted to word retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, PPA interventions rely mainly on speech training [9], and on promising approaches with noninvasive brain stimulation techniques [10][11][12] to counteract language de cits. However, it remains important to advance symptomatic treatment, to reduce disease burden and improve patients' and carers' quality of life [13].…”
Section: Introductionmentioning
confidence: 99%